Enhancing Technology Transfer on University Campuses Through Trainee-Led Grassroots Efforts: A Case Study of The BALSA Group and Fourth River Solutions - Austin, S. Kyle; Fiore, Chris; Goh, Saik-Kia; Schillebeeckx, Maximiliaan; L. Vanderford, Nathan; Maricque, Brett (Technology Transfer and Entrepreneurship (Discontinued), 2015)
The Biotechnology and Life Sciences Advising (BALSA) Group is a graduate studentand post-doctoral fellow-led strategic consulting firm dedicated to supporting economic growth and development in St. Louis, Missouri. BALSA has been recognized by St. Louis civic leaders as a valuable player in the St. Louis entrepreneurial community and has demonstrated that graduate students and post-doctoral fellows – without formal training – can provide professional business strategy support to start-ups, growing companies, and large corporations. The BALSA Group has inspired the establishment of similar groups around the United States, including Fourth River Solutions (4RS) at the University of Pittsburgh, in forming sustainable organizations that support their local entrepreneurial communities. Key to the success of new organizations are university Technology Transfer Offices, which can become recurring clients and serve as training grounds to build the core competencies of student-run consulting groups. This article highlights the success of The BALSA Group and 4RS in developing a novel addition to the Ph.D./post-doctoral fellow training paradigm, focusing on collaborations with Technology Transfer Offices, and describes a model for creating similar ventures at other universities.
Keywords: Academic commercialization